N, S co-doped biomass derived carbon with sheet-like microstructures for supercapacitors. (20th January 2020) - Ji, Linlin; Wang, Bin; Yu, Yanling; Wang, Nuoxin; Zhao, Jinbao
Abstract: In this study, N, S co-doped bamboo fiber derived carbon has been prepared when K3 Fe(CN)6 and thiourea are selected as graphitization catalysis and dopant, respectively. The derived carbon possesses a large SBET, suitable graphitization degree, excellent conductivity and wettability of electrolyte, and particularly, it exhibits a unique sheet-like microstructure derived from the layer stripping of gas produced by thiourea pyrolysis, and these microstructure features are very beneficial for energy storage. Typically, the derived carbon displays a high specific capacitance of 328 F/g and an acceptable rate capability of 61.3% at 15 A g −1 in three-electrode systems. Meanwhile, the derived carbon-based coin-type symmetric supercapacitors are assembled in an aqueous electrolyte and an ionic liquid electrolyte, respectively, and they all show a considerable synergetic energy-power output performance (21.2 Wh kg −1 at 454 W kg −1 in aqueous electrolyte, and 61.6 Wh kg −1 at 300 W kg −1 in ionic liquid electrolyte), indicating the potential application of the derived carbon in supercapacitors. Graphical abstract: Image 1 Highlights: Bamboo fiber derived carbon is prepared in the presence of K3 Fe(CN)6 and thiourea. The carbon exhibits a large SBET and a unique sheet-like microstructure. The carbon has a high specific capacitance (328 F/g) in three-electrode system. The carbon-based symmetric supercapacitors are assembled in aqueous and ionic liquid. The supercapacitor in ionic liquid displays a high energy density of 61.6 Wh kg −1 .